2007
DOI: 10.3354/meps333075
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in seaweed induced responses to herbivory

Abstract: Recent work on European (Swedish and English) populations of Ascophyllum nodosum has detected inducible defenses in response to snail grazing that include a decrease in algal palatability and an increase in phlorotannin concentration, a class of potential chemical defenses. However, tests of induced responses in other A. nodosum populations are lacking and we thus have a limited understanding of how widespread such responses are in fucoid algae. We exposed a North American (Massachusetts) A. nodosum population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…First, interstrain differences could produce the differing responses; Tang's P. globosa strain (CCMP 1528) was isolated from the Galapagos Islands, whereas ours (CCMP 627) was isolated from the Gulf of Mexico. Strains may respond differently to grazers given the recent discoveries that P. globosa is a multispecies complex (36) and that inducible responses to grazers can be population-or strain-specific (37,38). Second, our design prevented new cue production after filtrate collection, whereas Tang's design allowed for continuous cue production.…”
Section: Discussionmentioning
confidence: 99%
“…First, interstrain differences could produce the differing responses; Tang's P. globosa strain (CCMP 1528) was isolated from the Galapagos Islands, whereas ours (CCMP 627) was isolated from the Gulf of Mexico. Strains may respond differently to grazers given the recent discoveries that P. globosa is a multispecies complex (36) and that inducible responses to grazers can be population-or strain-specific (37,38). Second, our design prevented new cue production after filtrate collection, whereas Tang's design allowed for continuous cue production.…”
Section: Discussionmentioning
confidence: 99%
“…Long & Trussell 2007). For instance, previous research on a congeneric species to that used in the present study, Fucus radicans, has shown that it exhibits different adaptive traits regionally, due to restricted gene flow (Bergstr枚m et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The conditions for the evolution of inducible defenses have been amply investigated, but our understanding of variability of these responses, particularly over geographic scales, is still poor (Sanford et al 2003, Kishida et al 2007, Long & Trussell 2007). In the case of predators and their prey, although they typically coexist along large portions of their geographic ranges, often there are areas (e.g.…”
Section: Abstract: Inducible Defense 路 Escape Response 路 Predator-prmentioning
confidence: 99%